Effect of Shear Reinforcement on Flexural Strengths of Normal Weight and Palm-Kernel Shell Reinforced Concrete Beams - Olanitori, Lekan Makanju; Okusami, Jeremiah Ibukun (European Journal of Sustainable Development, 2019)
The focus of this research is to investigate the effect of shear reinforcement on flexural capacities of reinforced Normal Weight Concrete (NWC) and Palm Kernel Shell Concrete (PKSC) beams. Ten beams were cast: five from PKSC and five from NWC. The beams were with shear reinforcement spacing of 50 mm, 100 mm, 150 mm, 200 mm and without shear reinforcement respectively. The beams were loaded with a point load at beam centre, and the results showed that the flexural capacity of the beams decreases as the spacing of the shear reinforcements increases. The ultimate loads of PKSC beams were lesser than that of NWC beams by 9.0%, 7.1%, 14.5%, 21 and 26.8% for shear reinforcement spacing of 50 mm, 100 mm, 150 mm, 200 mm and for beam without shear reinforcements respectively. The deflections of the PKSC beams were greater than that of the NWC, hence the PKSC beams had more plastic rotation capacity than the NWC beams. The study shows that reinforced concrete beams produced from 20% partial replacement of crushed aggregate by PKS have the potential of being used for structural purposes in low cost buildings. Keywords: Palm Kernel Shell Concrete, Normal weight concrete, Palm kernel shell, Deflection, Shear reinforcement.